Analisis Uji Kuat Tekan Uniaksial Batupasir Pada Formasi Pamaluan, Kecamatan Longikis, Kabupaten Paser, Provinsi Kalimantan Timur - Musodiq Musodiq; Tommy Trides; Shalaho Dina Devy; Revia Oktaviani; Albertus Juvensius Pontus (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2023)
The uniaxial compressive strength test was carried out to determine the value of rock strength. This research was conducted on sandstones in the Pamaluan Formation. The tests carried out in this study were physical properties tests, compressive strength tests and grain size tests on sandstones with a total of 30 samples on the physical properties test, 10 samples on the mechanical test and 500 gram grain size test at each point, the purpose of which is to determine the effect of porosity on the compressive strength of rock. In testing the physical properties carried out, the lowest and highest porosity values ​​were 17.27 and 22.91%. The results of the compressive strength test with the lowest and highest values ​​were 3.05 and 7.63 MPa. The grain size test results at points 1 and 2 are the same, namely fine sandstones with a percentage of 45 and 44%. From the results of research that has been done the value of porosity and grain size is very influential on the compressive strength test.